Model Deep Dialogue/Critical Thinking Sebagai Wujud Wawasan Perbuatan dan Keterlibatan Kebangsaan yang Kritis dan Demokratis - M. Januar Ibnu Adham (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2021)
Abstract: The article aims to describe the efforts of teachers and students to practice good citizenship in the learning process, the paradigm process of citizenship demand, civic responsibility, and citizen participation in PPKn learning. The study used a qualitative design with classroom action research methods. The process filling in data at Kemmis and Taggart, namely Plan, Act & Observe, and Reflect, and data analysis techniques using Miles and Hubberman, namely data reduction, data presentation, levers. The result showed that students in applying the deep dialogue/critical thinking model showed students’ abilities it the aspects of intelligence, responsibility, honesty, and good citizenship. Through this application students can form representations in the completion of contemporary discussion themes that are able to create, have or show imagination and artistic or intellectual inventiveness (creative writing), and stimulate imagination and inventive power. And the implementation of Deep Dialogue/Critical Thinking in students of SMAN 1 Karawang can build an active group discource and also find the concept of cooperative learning which stimulates the effectiveness of classroom learning as a form of character education in youth creation with critical and democratic (community participation). Abstrak: Artikel ini bertujuan mendeskripsikan guru dan peserta didik dalam mempraktikan karakteristik warga Negara yang baik dalam proses pembelajaran, sebagaimana paradigma pembentukan civic intelligence, civic responsibility, dan civic participation pada pembelajaran PPKn. Penelitian kualitatif metode classroom action research ini, pengumpulan datanya merujuk pada Kemmis dan Taggart yaitu Plan, Act & Observe, dan Reflect serta analisis data menggunakan Miles dan Huberman yaitu reduksi data, penyajian data, verifikasi. Hasil penelitian menunjukan bahwa peserta didik dalam menerapkan model deep dialogue/critical thinking menunjukkan kemampuan siswa pada aspek intelligence, responsibility, honestly dan good citizenship. Melalui penerapan tersebut siswa dapat membentuk representasi dalam penyelesaian tema diskusi kekinian. Implementasi Deep Dialogue/Critical Thinking pada siswa di SMAN di Karawang dapat membangun diskursus kelompok yang bersifat aktif serta ditemukan juga konsep cooperative learning yang merangsang keefektifan pembelajaran dalam kelas sebagai wujud pendidikan karakter pada generasi muda dengan (civic participation) yang kritis dan demokratis. DOI: https://doi.org/10.33399/edukasia.v2i1.36